Association of Caribbean states : consolidation of the Greater Caribbean (ACS Port of SpainTT, 2002)
Includes country profiles. Focuses on major issues of concern to ACS such as globalization; regional integration; trade; trade negotiations; foreign relations; disaster management; transportation; tourism and telecommunications.
3rd Summit and 7th Ministerial Meeting December 2001